Spirometry-Related Pain and Distress in Adolescents and Young Adults with Cystic Fibrosis: The Role of Acceptance - Annabelle Casier; Liesbet Goubert; Tine Vervoort; Marleen Theunis; Danielle Huse; Frans De Baets; Dirk Matthys; Geert Crombez (Pain Research and Management)
OBJECTIVE: To investigate the occurrence of spirometry-related pain and distress in adolescents and young adults with cystic fibrosis (CF), and to investigate the role of acceptance of illness in spirometry-related pain and distress.